2022
DOI: 10.3390/en15124267
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Tight Sandstone Reservoir and Its Impacts on the Oil Migration and Accumulation: A Case Study of Shahejie Formation in Dongying Depression, Bohai Bay Basin

Abstract: The migration and accumulation of oil in tight sandstone reservoirs are mainly controlled by capillary force. Due to the small pore radius and complex pore structure of tight sandstone reservoirs, the capillary force is very sensitive to wettability, so wettability significantly affects oil migration and accumulation. However, the study of oil migration and accumulation in tight sandstone reservoirs often needs to combine multiple methods, the process is complex, and the research methods of wettability are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…During the simulation, the thermodynamic temperature T = 298.15 K, the temperature difference Δ T = 20, the ratio of r max0 to r min0 is 100, the friction coefficient of contact line ζ = 0.02 Pa·s, the capillary number Ca = 0.002, the pinning coefficient C pin = 5.6 mN/m, the smoothing parameter C = 2.5 × 10 4 , the elastic modulus E = 25 GPa, Poisson’s ratio υ = 0.25, the power law index β = 2/3, the shape factor F = 4, the linear expansion coefficient α = 1.4 × 10 –5 K –1 , constant B 1 = 8.038, constant B 2 = −1 × 10 3 , and the ultimate shear stress τ 0 = 50 Pa by laboratory tests . In general, there are various minerals in shale oil reservoirs, which result in the complicated wettability of shale oil porous materials . Based on experimental tests, many researchers have found that shale oil reservoirs were weak oil-wet. , Thus, for the sake of simplicity, in this work, the equilibrium contact angle θ e is assigned as 115°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the simulation, the thermodynamic temperature T = 298.15 K, the temperature difference Δ T = 20, the ratio of r max0 to r min0 is 100, the friction coefficient of contact line ζ = 0.02 Pa·s, the capillary number Ca = 0.002, the pinning coefficient C pin = 5.6 mN/m, the smoothing parameter C = 2.5 × 10 4 , the elastic modulus E = 25 GPa, Poisson’s ratio υ = 0.25, the power law index β = 2/3, the shape factor F = 4, the linear expansion coefficient α = 1.4 × 10 –5 K –1 , constant B 1 = 8.038, constant B 2 = −1 × 10 3 , and the ultimate shear stress τ 0 = 50 Pa by laboratory tests . In general, there are various minerals in shale oil reservoirs, which result in the complicated wettability of shale oil porous materials . Based on experimental tests, many researchers have found that shale oil reservoirs were weak oil-wet. , Thus, for the sake of simplicity, in this work, the equilibrium contact angle θ e is assigned as 115°.…”
Section: Resultsmentioning
confidence: 99%
“…32 In general, there are various minerals in shale oil reservoirs, which result in the complicated wettability of shale oil porous materials. 79 Based on experimental tests, many researchers have found that shale oil reservoirs were weak oil-wet. 80,81 Thus, for the sake of simplicity, in this work, the equilibrium contact angle θ e is assigned as 115°.…”
Section: Tpg Model Validationmentioning
confidence: 99%
“…The permeability attributes and efficiency of oil displacement via water injection in a reservoir are significantly influenced by its wettability [62,63]. It is clear that the relative wettability index of all samples, barring X4, shares a robust positive correlation with both the oil displacement efficiency in the non-aqueous phase and the ultimate oil displacement efficiency (Table 5 and Figure 17).…”
Section: The Relationship Between Micro-heterogeneity and Wettabilitymentioning
confidence: 98%
“…Regarding life cycle assessment, more energy is consumed to store up to 56% of CO 2 than is generated from the extra oil produced. Water-alternating gas (WAG) has also been exploited for the same purpose in EOR [57][58][59][60][61]; however, this injection strategy has not yet been applied or studied extensively in geological CO 2 storage in DSFs.…”
Section: Injection Strategy As a Means Of Reducing Wamentioning
confidence: 99%